IMPLEMENTASI KEBIJAKAN WPS DI TINGKAT PROVINSI DAN DAERAH: STUDI REALISASI RAD YOGYAKARTA (2022-2023) - M. Saifullah; Asa Zahara Januarsa; Petrina Ulayya Ramadhani; Raden Roro Kinthana Amodya Kusuma; Nur Assyahida Surya; Finka Syarief Hidayatullah (Pojok Publisher, 2025)
The landscape of security and peace continues to evolve. Over time, women have become a vital yet vulnerable group whose security is often at risk. However, the Women, Peace, and Security (WPS) agenda aims to promote well-being, equality, and respect for diversity, while also encouraging women's roles as agents of peace in fostering social cohesion and strengthening societal resilience across economic, social, and cultural domains. In Indonesia, the implementation of the RPA on WPS has been carried out through Regional Action Plans (RAD) across 12 provinces and 22 villages, including Yogyakarta. In this region, the agenda is supported by a specialized agency, the Office for the Empowerment of Women, Child Protection, and Population Control (DP3AP2), as well as the Governor of Yogyakarta's Regulation No. 12 of 2023. This research aims to analyze the implementation of Yogyakarta's RAD, which is derived from Indonesia's National Action Plan (RAN) on WPS. A qualitative approach is employed, with a tipping point analysis to evaluate how provinces and regions enact the WPS agenda through their respective RADs. Additionally, this study incorporates Cyber feminist theory to examine the role of social media in disseminating the WPS agenda to the public in Indonesia. Active participation by women’s organizations, supported by the implementation of RAD WPS, has the potential to raise awareness and responsiveness to violence against women. It also strengthens efforts to protect and empower women within the framework of policies and laws.